A quinoxalinone-derivated fluorescence sensor with optimized solubility for cysteine detection and biological imaging. (December 2019) - Zhang, Xu-Ping; Wang, Tian-Tian; Yuan, Zeng-Hui; Zhou, Yang; Yang, Yu-Shun; Zhu, Hai-Liang
Abstract: Factually, complicated and bulky molecular structures may impair the cell-permeating capability, which is still a challenge when developing sensors for biological imaging. Herein, as an essential optimization on practicability of our previous work, we attempted to raise an acrylate-containing quinoxalinone-derivated sensor with improved solubility to enhance the usability of Cys detection in living cells as well as in Caenorhabditis elegans . The optimized sensorQuiCys retained all the advantages such as high selectivity (over other thiols) and sensitivity (0.01 equiv.). Since the solubility was improved, other significant privileges including higher synthetic yield and better imaging potential stood out, which were important for practical applications. We then successfully promotedQuiCys to track Cys in vivo . More than providing an applicable tool for Cys detection, this work offered referable information for modification strategies of similar implements. Graphical abstract: For quantitative and selective detection of cysteine, we attempted to raise an acrylate-containing quinoxalinone-derivated sensorQuiCys with optimized solubility to enhance the usability in living cells as well as in Caenorhabditis elegans . It retained all the advantages such as high selectivity and sensitivity. Since the solubility was improved, other significant privileges including higher synthetic yield and better imaging potential stood out. We then successfully promotedQuiCys to track Cys in vivo, offering referable information for modification strategies of similar implements.Image 1 Highlights: Optimized solubility to enhance the usability in Cys detection. High selectivity over other thiols and good sensitivity. Practically improved imaging potential in living cells andsuccessfully promoted in Caenorhabditis elegans . Higher synthetic yield, more economic and practical.